Psychological Stress, Burnout and its relationship with Decision Making among Table Tennis Referees: A Case Study on the Fourth Championship of Saudi Universities - A. Abdul-Rah (Universidad de Murcia, 2018)
Background: Professional referees are exposed to external sources of stress more than ever before and the performance of match officials has recently come under increased attention and scrutiny. Purpose: The overarching aim of this study was to investigate the psychological stress related to decision making and their relation to psychological burnout among table tennis referees in the fourth championship of Saudi universities. The research tool was applied to a sample of 20 referees who participated in the championship. Method: Psychologcal Stress scale constructed by Mustafa and Abdoul (2001) (23 items) was used to measure the psychological stress related to decision making among the referees. Further, in order to measure Referee's psychological burnout concerning the intensity and frequency a 23 items scale devised by Al-Haramlah (2016) was implemented. An acceptable validity and reliability were calculated for both the scales were found significant. Result: The study showed that, psychological pressures experienced by the table tennis referees which are connected to the difficulty encountered by referees in taking judgment of the refereeing crew as a result of the over-tension during the game. The referees' also percept a feeling of anxiety and stress while making any decision to settle the results of the match in the final minutes. Conclusion: The results of the study revealed a positive correlation between the psychological stress related to decision making and emotional burnout associated with intensity among table tennis referees.